Microfluidic Chip for Quantitatively Assessing Hemorheological Parameters - Yang Jun Kang (Micromachines)
The biomechanical properties of blood are regarded as promising biomarkers for monitoring early-stage abnormalities and disease progression. To detect any changes in blood, it is necessary to measure as many rheological properties as possible. Herein, a novel method is proposed for measuring multiple rheological properties of blood using a microfluidic chip. The syringe pump turns off for 5 min to induce RBC (red blood cell) sedimentation in the driving syringe. RBC aggregation is determined by analyzing the time-lapse blood image intensity at stasis: I(t) = I1 exp (−k1t) + I2 exp (−k2t). RBC-rich blood and RBC-depleted blood are sequentially infused into the microfluidic chip. Based on blood pressure estimated with time-lapse blood velocity, blood viscosity is acquired with the Hagen–Poiseuille law. RBC sedimentation is quantified as RBC sedimentation distance (Xesr) and erythrocyte sedimentation rate (ESR). The proposed method provides a consistent viscosity compared with previous methods. Two of the four variables (I1, I2) exhibited a strong correlation with the conventional RBC aggregation index (AI). The indices Xesr and ESR showed consistent trends with respect to the blood medium and hematocrit. In conclusion, the proposed method is then regarded as effective for monitoring multiple rheological properties.